Open data: Examining the lateralization of electrophysiological correlates of auditory awareness - Wiens, Stefan; Gerdfeldter, Billy (Stockholm University, 2024)
Supplementary material for the associated publication.

ABSTRACT

The neurological basis for perceptual awareness remains unclear, and theories disagree as to whether sensory cortices per se generate awareness. Critically, neural activity in the sensory cortices is only a neural correlate of consciousness (NCC) if it closely matches the contents of perceptual awareness. Research in vision and touch suggest that contralateral activity in sensory cortices is an NCC. Similarly, research in hearing with two sound sources (left and right) presented over headphones also suggests that a candidate NCC called the auditory awareness negativity (AAN) matches perceived location of sound. The current study used 13 different sound sources presented over loudspeakers for natural localization cues and measured event-related potentials (ERPs) to a threshold stimulus in a sound localization task. Preregistered Bayesian mixed models provided moderate evidence against an overall AAN and very strong evidence against its lateralization. Because of issues regarding data quantity and quality, exploratory analyses with aggregated data from multiple loudspeakers were conducted. Results provided moderate evidence for an overall AAN and strong evidence against its lateralization. Nonetheless, the interpretations of these results remain inconclusive. Therefore, future research should reduce the number of conditions and/or test over several sessions to procure a sufficient amount of data. Taken at face value, the results may suggest issues with AAN as an NCC of auditory awareness, as it does not laterally map onto experiences in a free-field auditory environment, in contrast to the NCCs of vision and touch.

ETHICS STATEMENT

Ethical review and approval were not required for studying human subjects in accordance with local law and institutional requirements, as we did not collect personal and biological data that can be traced back to the subject. The experiment adhered to the declaration of Helsinki. Subjects were required to provide their written informed consent to participate in this study and that their raw data will be shared in anonymized form.

The uploaded data are considered anonymized because there is no key that links test subjects to their data.

DATE & LOCATION OF DATA COLLECTION

Subjects (N = 56; Final sample: N = 37) were tested between August 2022 and October 2022 at the Department of Psychology, Campus Albano, Stockholm, Sweden.

DATA & FILE OVERVIEW

See readme file for details.
Keywords: Psychophysiology; Cognitive neuroscience; Sensory processes, perception and performance; Neurosciences; Neurovetenskaper